A study on the LC procedures of Bridge Chemie and a comparison of the profit margin between imported and locally manufactured machines - Rahman, Minhazur (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.